Actuarial decision-making: the example of Bordeaux red wine auctions - Aldag, Ramon J. (Henry Stewart Talks, 2019)
This insight looks at the difference between clinical and actuarial decision making, and as an example looks at how actuarial decision making is used to predict the prices of luxury wines many years before the prices are determined at auctions.
Archived at 2024/02/11